Radiation chemistry comes before radiation biology. - O'Neill, P; Wardman, P (2009)
PURPOSE: This article seeks to illustrate some contributions of radiation chemistry to radiobiology and related science, and to draw attention to examples where radiation chemistry is central to our knowledge of specific aspects. Radiation chemistry is a mature branch of radiation science which is continually evolving and finding wider applications. This is particularly apparent in the study of the roles of free radicals in biology generally, and radiation biology specifically. The chemical viewpoint helps unite the spatial and temporal insight coming from radiation physics with the diversity of biological responses. While historically, the main application of radiation chemistry of relevance to radiation biology has been investigations of the free-radical processes leading to radiation-induced DNA damage and its chemical characterization, two features of radiation chemistry point to its wider importance. First, its emphasis on quantification and characterization at the molecular level helps provide links between DNA damage, biochemical repair processes, and mutagenicity and radiosensitivity. Second, its central pillar of chemical kinetics aids understanding of the roles of 'reactive oxygen species' in cell signalling and diverse biological effects more generally, and application of radiation chemistry in the development of drugs to enhance radiotherapy and as hypoxia-specific cytotoxins or diagnostic agents. The illustrations of the broader applications of radiation chemistry in this article focus on their relevance to radiation biology and demonstrate the importance of synergy in the radiation sciences. CONCLUSIONS: The past contributions of radiation chemistry to radiation biology are evident, but there remains considerable potential to help advance future biological understanding using the knowledge and techniques of radiation chemistry.